PENGEMBANGAN PEMBELAJARAN TEKS PIWULANG SERAT WULANGREH PUPUH GAMBUH DENGAN MEDIA ANIMASI TEMBANG UNTUK SISWA KELAS VIII SMP NEGERI 1 CILACAP - Az-zahra, Oktaviani Wilfa (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2019)
Text learning of Serat Wulangreh is text learning material of Serat Wulangreh written by Sri Susuhunan Pakubuwana IV which covered values and lifes. Students difficulties in understanding the content of the material are the basis for arranging learning devices which is in the form of RPP and audio-visual media as the supporting devices. Research methodology used a research and development approach with five stages, they were: identifying of potential and problems, collecting data, product design, design validation and design revision. Collecting data instrument included observation guideline, interview guideline, necessity questionnaires, validation of media expert, material expert, and teacher. The product design contained of two verses Tembang Gambuh recording video with life story animated illustration based on the main content of Tembang Gambuh text. The video also was completed with text translation in Banyumas dialect. The validaton test result showed that the average score was 4,3 points from the media expert, 4 points from material expert, and 4 point from the teacher. Overall, the validation test result of product shows that the average score was 4 points which means the product design was categorized as good assessment.